The FINITE ELEMENT ANALYSIS OF L-SHAPE BUILDING AND ITS SEISMIC BEHAVIOUR VARIATIONS IN E-TABS - VIJAYA KUMAR M; Sonia B M (PREPARE@u® | IEI Conferences, 2021)
ETABS is the structural software which is mostly used to analyze steel and concrete structures, low and high rise buildings, portal frames and skyscraper structures. In this project we had studied structural behavior of L-shaped commercial multi-Storey building (college building) of G+5 on etabs. Here, structural analysis of the building was carried using equivalence static or linear static analysis method as per IS1893:2002. In this method the design base shear is computed for the whole building, and then it is distributed along the height of the building. This method defines that a series of forces acting on a structure to represent the effect of earthquake ground motion. In this project we had compared the result obtained from the etabs software with the manual calculations and concluded that the percentage of error between both the results or within the permissible limit. Here, the longer beam span shows more deflection so secondary beams can be considered to avoid more deflections. It shows that masonry infill walls will help in increasing the strength, stiffness and ductility of the structure.